Acylsilanes in Rhodium(III)‐Catalyzed Directed Aromatic C–H Alkenylations and Siloxycarbene Reactions with CC Double Bonds1. Issue 1 (19th November 2013) - Becker, Peter; Priebbenow, Daniel L.; Pirwerdjan, Ramona; Bolm, Carsten
Abstract Acylsilanes are known to undergo a 1, 2‐silicon‐to‐oxygen migration under thermal or photochemical conditions to form siloxycarbenes. However, there are few reports regarding the application of siloxycarbenes in organic synthesis and surprisingly, their reaction with CC double or triple bonds remains virtually unexplored. To facilitate such a study, previously inaccessible aromatic acylsilanes containing an ortho‐tethered CC double bond were identified as suitable substrates. To access these key intermediates, we developed a new synthetic method utilizing a rhodium‐catalyzed oxidative Heck‐type olefination involving the application of an acylsilane moiety as a directing group. When exposed to visible‐light irradiation, the ortho‐olefinated acylsilanes underwent a smooth intramolecular cyclization process to afford valuable indanone derivatives in quantitative yields. This result paves the way for the development of new transformations involving siloxycarbene intermediates.